Wear - resistance of reinforced structural steel surfaces in active corrosive environments - Стечишин, М.С.; Форкун, В.В.; Береговий, А.І.; Білик, Ю.М. (Problems of Tribology, 2014)
The paper examines cavitational wear-resistance of steels of following types: steel 45. 15Chr and 40Chr - after thermal cyclic processing (ThCP)), low-temperature ion nitriding and by depositioning of protective polymer coatings in model and real milk processing factory environments